INTERNET, TELEVISION AND MOBILE TECHNOLOGIES FOR INNOVATIVE ELEARNING - Kapenieks, Atis; Zuga, Bruno (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
We are developing an innovative cross-media learning delivery system (eBig3, ETM) that goes beyond traditional web-based learning approaches. The approach combines wide availability of television and mobile technologies with the capacity and flexibility of Internet based e-learning. This approach allows the learner to use either a single learning delivery system (depending on availability and preferences) or a complementary combination of two or three delivery systems, thus supporting the anywhere, anytime — by any preference—learning paradigm. The development of the eBig3/ETM learning solutions includes integration of technical aspects of cross-media learning content delivery. Moreover, the approach incorporates pedagogical and usability principles based on an understanding of the target users learning needs and their contexts.